A new strategy of interlayer doping of Li ions for the photoluminescence enhancement of Eu3+-doped bismuth oxychloride layered semiconductors. Issue 17 (27th July 2020) - Fan, Youzhun; Han, Jiajun; Xiao, Taizhong; He, Fangyu; Peng, Jincai; Wang, Qi; Li, Yongjin; Yin, Zhaoyi; Yang, Zhengwen; Qiu, Jianbei; Fu, Hao; Song, Zhiguo
Abstract : The interlayer doping of Li + ions significantly improves the IEF in layered BiOCl, which modifies the photoluminescence of Eu 3+ ions via its local field effect and photocarrier separation role. Abstract : Lattice modification by Li + doping has been an effective method to manipulate the optical property of lanthanide-doped phosphors, but it lacks an understanding for the highly anisotropic layered host connected by van der Waals forces. In this work, based on BiOCl layered crystals prepared by the solid-state method, we systematically studied the doping mechanism of Li + ions and its effects on the luminescence properties of Eu 3+ activators. The experiment and calculation results indicated that high-concentration Li + ions can be incorporated into the lattice interlayer by van der Waals forces rather than into substitutional or interstitial sites. Moreover, Li + ion dopants greatly decrease the crystallinity of BiOCl samples but improve their interlayer electrostatic potential and spontaneous internal electric field (IEF). When the doping concentration increased to 30% moles, the emission intensity of Eu 3+ ions under host excitation is enhanced by at least 5 times, accompanied with the prolonged decay time. With the interlayer doping of Li + ions, the local field effect and photocarrier separation role of the enhanced IEF are responsible for the special photoluminescence properties of Eu 3+ ions. The results of this paper not only contribute to understand the optical and structural properties of the layered phosphor system but also open up new ideas for the construction and design of efficient photonic materials.